IT Support Website Security Evaluation Using Vulnerability Assessment Tools - Armando, Rio; Melyantara, I G Ag Kom Agnam; Elfariani, Rizma; Latuconsina, Desy Fitri Aulia; Nasrullah, Muhammad (Journal of Information Systems and Informatics, 2022)
Vulnerability Assessment is one of the crucial stages that must be carried out to define and identify vulnerabilities in web systems so that they can be repaired and reduced. The XYZ institution is new, so the Vulnerability Assessment is to minimize attacks from irresponsible parties. In this study, a Vulnerability Assessment of the IT Support website was carried out on XYZ institution using the Nessus tool. This study used the Vulnerability Assessment Penetration Testing (VAPT) Life Cycle method, which has six stages: scope, planning, scanning & vulnerability Analysis, exploitation, Privilege Escalation, and Generating Report. The results of this study obtained various vulnerabilities ranging from Low to Critical on the IT Support website at XYZ institution so that the IT Support party at XYZ institution to update PHP versions, JQuery and several other preventive steps reviewed in the discussion section.